Demography as the basis for understanding and predicting range dynamics. Issue 12 (December 2014) - Normand, S.; Zimmermann, N. E.; Schurr, F. M.; Lischke, H.
<x xml:space="preserve">Abstract</x> Demographic processes and demographic data are increasingly being included in models of the spatio–temporal dynamics of species' ranges. In this special issue, we explore how the integration of demographic processes further the conceptual understanding and prediction of species' range dynamics. The 12 papers originate from two workshops entitled 'Advancing concepts and models of species range dynamics: understanding and disentangling processes across scales'. The papers combine theoretical and empirical evidence for the interplay between environmental conditions, species interactions, demographic processes (births, deaths, dispersal), physiology, and evolution, and they point out promising avenues towards a better understanding and prediction of species' range dynamics.